Why do users accept the information technology? Description and use of theories and models of their acceptance - García De Blanes Sebastián, María; Artonovica, Arta; Sarmiento Guede, José Ramón (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The objective of this research is to understand, predict and explain what factors influence organizations and induce individuals to accept technology. Through the methodology of content analysis and based on the Web of Science database and through the MAXQDA software, this document analyzes and reviews the ten most important theories and models of technology acceptance used in recent years. This review offers a holistic view that will help future researchers to select the most appropriate theories to apply to their field of study.